Tratamiento informativo sobre el caso “sobornos 2012 - 2016” publicado en la plataforma digital del Diario El Comercio, enero - junio 2020. - Andrés Santiago, Haro Suárez (2021)
ABSTRACT This research project: INFORMATION TREATMENT ON THE CASE "BRIBES 2012 - 2016" PUBLISHED ON THE DIGITAL PLATFORM OF DIARIO EL COMERCIO, JANUARY - JUNE 2020. It was carried out to identify which was the informational treatment that the media gives the most relevant corruption case in Ecuador called "Bribes 2012 - 2016" published on the website of Diario El Comercio. In the methodological application, scientific and analytical methods were used; The type of research is qualitative - quantitative. On the other hand, the research design is descriptive and analytical. Through the application of the content analysis files, it was possible to show how the media builds journalistic products to be published on its digital platform. With the execution of the interviews, the specialists' criteria were obtained, and it was possible to delve into specific topics of the research work. This research project registers that Diario El Comercio has followed this corruption case from the beginning, producing journalistic content from different communication axes, using various journalistic genres, stories such as; Informative note, Opinion article, Editorial, Interview, and Chronicle. Finally, an audiovisual journalistic report was made on the case "Bribes 2012 - 2016", in which all the relevant information collected in the research project is recorded. Keywords: "Bribes 2012 - 2016", corruption, digital platform, journalistic content. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR C.C. 0603356783